2021
DOI: 10.3390/ijms22020809
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed Electromagnetic Field Stimulation in Osteogenesis and Chondrogenesis: Signaling Pathways and Therapeutic Implications

Abstract: Mesenchymal stem cells (MSCs) are the main cell players in tissue repair and thanks to their self-renewal and multi-lineage differentiation capabilities, they gained significant attention as cell source for tissue engineering (TE) approaches aimed at restoring bone and cartilage defects. Despite significant progress, their therapeutic application remains debated: the TE construct often fails to completely restore the biomechanical properties of the native tissue, leading to poor clinical outcomes in the long t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(72 citation statements)
references
References 82 publications
0
46
0
2
Order By: Relevance
“…It is widely accepted that PEMF exposure can promote osteogenesis, stimulating the osteoblast differentiation of human bone mesenchymal stem cells (hBMSCs). Indeed, this exposure has been successfully applied to improve bone regeneration in skeletal diseases and fractures (Ongaro et al 2014 ; Varani et al 2021 ). In order to investigate the molecular mechanisms behind this phenomenon, De Mattei et al ( 2020 ) assessed whether PEMF exposure can modulate the expression of miRs involved in osteogenic differentiation.…”
Section: Elf-mf Exposure Effects On Epigenetic Marksmentioning
confidence: 99%
See 1 more Smart Citation
“…It is widely accepted that PEMF exposure can promote osteogenesis, stimulating the osteoblast differentiation of human bone mesenchymal stem cells (hBMSCs). Indeed, this exposure has been successfully applied to improve bone regeneration in skeletal diseases and fractures (Ongaro et al 2014 ; Varani et al 2021 ). In order to investigate the molecular mechanisms behind this phenomenon, De Mattei et al ( 2020 ) assessed whether PEMF exposure can modulate the expression of miRs involved in osteogenic differentiation.…”
Section: Elf-mf Exposure Effects On Epigenetic Marksmentioning
confidence: 99%
“…Several studies showed that electromagnetic fields can modulate processes that involve epigenetic mechanisms, such as cell commitment (Maziarz et al 2016 ) and neuronal and osteogenic differentiation (Leone et al 2015 ). Because of these effects, magnetic fields are considered of interest for therapeutic interventions, including repair of tissue injury and development of bone (Varani et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Endogenous growth factors, cytokines and signals from the extracellular matrix, mainly via integrin interactions, represent essential regulators in cell differentiation [7,8]. Further, external stimuli, such as mechanical forces or electromagnetic fields, modulate cell behavior during osteogenesis [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…MiRNAs are small, single-stranded, non-coding RNAs consisting of approximately 21-25 nucleotides (nt) and expressed in many organisms, from viruses [29][30][31] to eukary- Endogenous growth factors, cytokines and signals from the extracellular matrix, mainly via integrin interactions, represent essential regulators in cell differentiation [7,8]. Further, external stimuli, such as mechanical forces or electromagnetic fields, modulate cell behavior during osteogenesis [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Mobility is reduced because of the tumor and a role of physiotherapist comes there itself. In this case the osteochondroma is of ribs so, the lung functions are affected as well [8,9]. The goal includes maintaining the lung compliance Costal osteochondroma is a rare but important condition to recognize due to its complications, such as reduced range of movement, pain, cosmetic abnormalities and bursitis.…”
Section: Discussionmentioning
confidence: 99%